Zasada ogólna czynnego udziału strony w postępowaniu administracyjnym a prawa strony w postępowaniu w sprawach załatwianych milcząco - Gajda-Durlik, Małgorzata (Wydawnictwo Naukowe UAM, 2019)
Pursuant to the amendment to the Code of Administrative Procedure, the Act of 7 April 2017 amending the Act – The Code of Administrative Procedure and certain other acts, the settling of a matter quietly has been incorporated into the framework of this Code. The legislator reserved a peculiar procedural regime for cases settled quietly, based on the formula of simplified, de-formalised proceedings, with simutaneous setting of limits for the rights of the party in the trial. Pursuant to Article 122d § 1 of the Code of Administrative Procedure, the provisions of Articles 10 and 79a of the Code of Administrative Procedure shall not apply to matters settled quietly. There is no doubt that the addition to Section II of the Code of Administrative Procedure of Chapter 8a on quiet settlement of matters results in the application of the Code of Administrative Procedure to matters within this scope, including, inter alia, Article 28 of the Code – on the side of proceedings. This means that in matters settled quietly, similarly as in the case of matters settled by an administrative decision, the subjective scope of proceedings is determined by Article 28 of the Code of Administrative Procedure, stating that each party is a party whose legal interest or duty the proceedings relate to, or who demands the authority to act due to its legal interest or duty. At the same time, the reservation made in Art. 122a § 2 of the Code of Administrative Procedure that a case is deemed to have been settled quietly when the party’s claim has been fully accepted does not mean in practice that only homogeneous interests of the party or parties expressed in the claim are involved in the case, and that the legal interests of subjects not filing a claim will not be involved in the case. As a consequence of the above, the fundamental question arises as to what extent the provision of Article 122d(1) of the Code of Administrative Procedure interferes with the conventional system of guaranteeing the rights of a party or parties adopted for cases settled in the jurisdiction process. The starting point of the analysis is the identification of the basic standard for determining the procedural position of a party in administrative proceedings, and then confronting with the solutions of the institution of quiet settlement of the matter in the scope different from the standard.
The general principle of active participation of a party in administrative proceedings and the rights of a party in proceedings in cases settled quietly
Keywords: party to proceedings; principle of active participation of a party in proceedings; institution of a quiet settlement of a case